Based on the Zero Property (also known as the Zero Product Property), if the product of two factors equals zero, then at least one of the factors must be equal to zero.
For the quadratic equation given, (2x – 3)(x + 2) = 0, this means:
- If (2x – 3) = 0, then \(x = \frac{3}{2}\)
- If (x + 2) = 0, then \(x = -2\)
Thus, at least one of the factors must equal zero for the entire equation to equal zero.
Therefore, the correct answer is:
C. At least one of the factors, (2x – 3) or (x + 2), must equal 0 for the entire function to equal 0.